Assessment of suitable minimum ecological flow downstream of a dam in the Upper Yellow River based on native fish conservation. Issue 1 (30th December 2022) - Yang, Lu; Hou, Jingming; Tong, Yu; Wang, Pan; Cheng, Long; Song, Ce; Yuan, Liu; Lv, Jiaojiao; Xue, Shuhong
Abstract: To ensure the ecological operation of the proposed C hydropower stations of the Upper Yellow River, the suitable minimum ecological flow of the study reach after the completion of hydropower station is studied. The native plateau fish was considered as an indicator species of the reach downstream of the dam for ecological conservation. The study is based on a 2D shallow water model with high-precision solution methods and GPU-accelerated performance, combined with Tennant, hydraulics method and habitat suitability models to obtain habitat conditions of river for fish survival during non-spawning periods and effective habitat areas during spawning period under different discharges. The results indicated that the suitable minimum ecological flow downstream of the C hydropower station was 87.5 m³/s to protect fish downstream. This achievement not only provides basic data for the optimal operation of C hydropower station based on the ecological response, but also some reference value for the actual operation management of water conservancy projects. Besides, it is of great ecological significance for the protection of native fish habitat in the Yellow River Basin. Graphical Abstract